MODERNISASI PEMBELAJARAN FISIKA: MGMP IPA CILEGON INTEGRASIKAN DEEP LEARNING DAN PHET DALAM MATERI GETARAN, GELOMBANG, DAN BUNYI - Guntara, Yudi; Khairunnisa, Khairunnisa; Septiani, Nia; Listiyani, Hanum; Nurfadilah, Annisa; Muna, Chynta Nadya; Dewi, Sharani; Hakim, Hafied Rahman (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
Physics is often considered a challenging subject due to its abstract nature of matter and requires high visualization, especially on the topics of vibration, waves, sound, light, and optics. To overcome this, the Subject Teacher Meeting of Cilegon City Junior High School together with Physics Education lecturers FKIP Untirta held an innovative training that integrated the Deep Learning approach and PhET interactive simulation media. The training was carried out in two sessions at SMPN 5 and SMPN 1 Cilegon City involving 32 science teachers. Activities include identification of needs, delivery of contextual pedagogical materials, video playback of physics phenomena, PhET simulation practice, and interactive discussions. The results of the evaluation showed that 85–90% of participants experienced an increase in understanding of physics concepts and an interest in visual and exploratory learning methods. These findings indicate that the integration of Deep Learning and PhET can enrich physics learning to be more contextual, engaging, and aligned with 21st century competencies. This program is the first step towards the transformation of sustainable education with teachers as drivers of innovation.